Identifying Dimensions of hospital cost management in Iranusing structural equation modeling - Ghaziasgar, Mahsa; Vahdat, Shaghayegh; Hessam, Somayeh; asl, Iravan Masoudi; Tabrizi, Hosein Moshiri (The journal of contemporary issues in business and government, 2021)
Aim: Hospitals as the most important providers of healthcare services around the world, are facing a wide range of duty and cost of services. This article aimed to identifying the key dimensions affecting in the cost management of Iran hospitals. Methods: This descriptive study was performed in two qualitative and quantitative stages. First factors influencing hospital cost management were extracted through literature and interview with 20 experts in the field of hospital governance and proposed model was designed. Then a questionnaire was developed and data was collected from 207 experts in the staff-and-line sector of Tehran University of medical sciences. The research model was analyzed using exploratory and confirmatory factor analysis in SPSS22 and Lisrel software. Results: Five dimensions influencing hospital cost management were identified. Human resource management and consumption resource management with factor of 0.88 and 0.71 had the most and least significant efforts on hospital cost management. Conclusions:This finding revealed that, for optimal hospital cost management, while considering all five factors, human resource management should be emphasized.